School choice in Indigenous families as a conflicting path between territories and cultures: The case of rural Mapuche families in Chile - Juan De Dios Oyarzun; Laura Luna; Camila Moyano (The Australian Journal of Indigenous Education)
Chile has a highly segregated education system. Indigenous students tend to be one of the most disadvantaged socio-cultural groups in terms of educational access and academic outcomes, in addition to lacking consistent intercultural educational alternatives. Through in-depth interviews, we explored Mapuche families’ experiences from two communities in rural southern Chile regarding their secondary school choice processes. This study analyses ethnic, territorial and future labour-related aspects influencing families’ decisions regarding their children’s educational transition. Generally, the path from primary to secondary school in rural settings involves a change from a small, local, multi-grade primary school to an urban secondary school. The findings show that this decision involves the crossing of ethnic, territorial and social boundaries that affect the families’ educational definitions related to the aspirational expectations for their children. In this, secondary school choice appears as an event in which different aspects and tensions of contemporary Indigenous ethnicity emerge and are confronted.